BKKBN Counseling Method for Pregnant Women in Preventing Babies with Stunting - Alya Rojwa Darus; Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2023)
Fulfillment of balanced nutrition at 1000 HPK is very important for children. Inadequate nutrition will have an impact on the growth and development of children. This is often referred to as stunting. Especially in the current era, the government gives responsibility to BKKBN in reducing the number of stunting at birth that occurs in Indonesia. The purpose of this study was to find out the methods of stunting counseling carried out by BKKBN for pregnant women in preventing babies with stunting. This research was conducted using a descriptive qualitative method. Respondents in this study were BKKBN extension workers in Tanjung Pura District. The research results obtained were counseling methods carried out by the BKKBN for pregnant women in preventing babies with stunting, namely using the discussion method. This method is effective in providing understanding to pregnant women about stunting and its prevention. However, prevention cannot be done only through counseling, it must be adjusted again to the conditions and situation of pregnant women.